THE IMPORTANCE OF DOING AN ICE-BREAKING BEFORE CORE LEARNING ACTIVITIES - Farah Amaliyah Yuwono; Rahmania Sri Untari; Lintang Suminar; Ristananda Izzul Muslimin Syifa (P3I UMSurabaya, 2024)
This study discussed the importance of doing an Ice-Breaking before Core Learning Activities to enhance students’ learning motivation level for Tenth grade students at SMKN 2 BUDURAN SIDOARJO. This research objectives to avoid of students’ problem that exhibiting low enthusiasm and motivation in their learning endeavors. The researchers employed a qualitative descriptive methodology. The techniques for data collection encompassed observation, doing three categories of ice-breaking, and documentation only. The findings showed the data of participants consisted around +30 students from various classes, specifically X DKV, RPL, and BD classes and showed the attachment of three categories of ice-breaking techniques were applied across several classes, specifically